Overview of Clinical Relevance of Antibodies Against Oxidized Low-Density Lipoprotein (oLAb) Within Three Decades by ELISA Technology - Willibald Wonisch; Franz Tatzber; Meinrad Lindschinger; Andreas Falk; Ulrike Resch; Sabrina Mörkl; Neven Zarkovic; Gerhard Cvirn (Antioxidants)
One of the most prominent actions of oxidative stress is the attack of free radicals on poylyunsaturated fatty acids (PUFAs), initiating a chain reaction to modify these PUFAs and generate oxidized modifications on all biomolecules. In the last quarter of the 20th century, intensive research was carried out to identify antibodies against such modifications. In the mid-1990s, the first enzyme-linked immunosorbent assay (ELISA) was introduced to the market, significantly accelerating research activities and knowledge gain. During this pioneering period, the main focus was on cardiovascular diseases, cancer, diabetes, and other diseases associated with oxidative stress. Subsequently, a standard range of these antibodies against oxidized LDL (oLAb) was determined in the population. Furthermore, the impact of exhaustive physical activity and diet on oLAb titers, and the correlation between newborns and mothers after delivery, as well as nutritional intake in newborns, were evaluated. Subsequently, the harmful effects of smoking and many other areas regarding oLAb titer were published, resulting in novel approaches for prognostic and therapeutic options, in particular through studies with antioxidants, which were able to influence oLAb significantly. This review presents an overview of the research activities obtained with this ELISA over the past three decades.